2016
DOI: 10.1111/ajco.12471
|View full text |Cite
|
Sign up to set email alerts
|

Compression use during an exercise intervention and associated changes in breast cancer-related lymphedema

Abstract: Our findings demonstrated an absence of a positive or negative effect from compression use during exercise on lymphedema. Current and previous findings suggest the clinical recommendation that garments must be worn during exercise is questionable, and its application requires an individualized approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
1
14
0
2
Order By: Relevance
“…Only 1 study directly assessed compression garment use during exercise. Singh et al 74 (lI) compared individuals with BCRL performing an episode of moderate load resistance exercise with or without compression (23–32 mmHg). No significant difference ( P = .89) in limb volume was found in either group at 24-hour follow-up.…”
Section: Interventions Recommended For Individuals Diagnosed With Bcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 study directly assessed compression garment use during exercise. Singh et al 74 (lI) compared individuals with BCRL performing an episode of moderate load resistance exercise with or without compression (23–32 mmHg). No significant difference ( P = .89) in limb volume was found in either group at 24-hour follow-up.…”
Section: Interventions Recommended For Individuals Diagnosed With Bcrmentioning
confidence: 99%
“…Because all level I/II articles reviewed involved some level of compression wear during aerobic and resistive exercise, compression garments may be worn to mitigate risk of exacerbation. According to Singh et al, 74 if an individual did not wear a compression garment while performing moderate load resistive exercise, the risk for short-term exacerbation was likely minimal.…”
Section: Interventions Recommended For Individuals Diagnosed With Bcrmentioning
confidence: 99%
“…Furthermore, Svensson et al (1994) showed that arm venous drainage has some problem in breast cancer survivors with lymphedema (39); thus, stretching exercises may reduce tissue hardness, and trapped lymph fluid (38). surveyed the effect of 12 weeks of exercise training with a compression bandage on lymphedema changes in women with breast cancer (40). They observed compression use during exercise training had no positive or negative effect on breast cancer-related lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…[37,44] Resistance exercise programs have been shown to have a positive effect on arm function and muscular strength without increasing the arm volume in BCRL patients. [47] Although some small-scale studies have demonstrated an absence of positive and negative effect from compression use during exercise on lymphedema, [48] some authors have suggested the use of pressure garments during exercise. [37,44]…”
Section: Manual Lymphatic Drainagementioning
confidence: 99%